Potential of conserved antigenic sites in development of universal SARS-like coronavirus vaccines - Wang, Siling; Wu, Dinghui; Xiong, Hualong; Wang, Juan; Tang, Zimin; Chen, Zihao; Wang, Yizhen; Zhang, Yali; Ying, Dong; Lin, Xue; Liu, Chang; Guo, Shaoqi; et al. (Frontiers in Immunology, 2022)
Given pandemic risks of zoonotic SARS-CoV-2 variants and other SARS-like coronaviruses in the future, it is valuable to perform studies on conserved antigenic sites to design universal SARS-like coronavirus vaccines. By using antibodies obtained from convalescent COVID-19 patients, we succeeded in functional comparison of conserved antigenic sites at multiple aspects with each other, and even with SARS-CoV-2 unique antigenic sites, which promotes the cognition of process of humoral immune response to the conserved antigenic sites. The conserved antigenic sites between SARS-CoV-2 and SARS-CoV can effectively induce affinity maturation of cross-binding antibodies, finally resulting in broadly neutralizing antibodies against multiple variants of concern, which provides an important basis for universal vaccine design, however they are subdominant, putatively due to their lower accessibility relative to SARS-CoV-2 unique antigenic sites. Furthermore, we preliminarily design RBDs to improve the immunogenicity of these conserved antigenic sites. Our study focusing on conserved antigenic sites provides insights for promoting the development of universal SARS-like coronavirus vaccines, thereby enhancing our pandemic preparedness.